Offline imaging of positron emitters induced by therapeutic helium, carbon and oxygen ion beams with a full-ring PET/CT scanner: experiments in reference targets - Bauer, Julia; Debus, Jürgen (Physics in medicine and biology, 2019)
In vivo verification of light ion therapy based on positron-emission tomography (PET) imaging of irradiation induced patient activation relies on activity predictions from Monte-Carlo (MC) or analytical computational engines for comparison to the measurements. In order to achieve the necessary accuracy, experimental data are indispensable for the validation of the calculation models. For this we irradiated thick reference targets with mono-energetic helium, carbon and oxygen ion beams and measured the resulting material activation offline with a commercial full-ring PET/CT scanner located nearby the treatment room. Acquired PET data were analysed over time to separate the activity contribution of different radionuclides. Determined production yields were compared to published findings obtained from in-beam activation measurements with a limited-angle double-head PET camera. In addition, we investigated the time-dependence of the measured radionuclide-specific contributions and of the distal activity range, as well as the lateral spread of the activity signal as a function of beam penetration depth. We present radionuclide-specific depth-resolved activity distributions and production yields for the radionuclides , and , dominating irradiation-induced patient activation. We observe systematically lower production yields with a ratio between the dual-head and our full-ring PET measurements of, on average, 1.7 and 1.3 for the oxygen and carbon beam irradiations, and 1.7 (2.1) for the high (low) energy helium beam irradiations. Findings on the temporal development of the activity range confirm the expectation, with the oxygen beam induced signal being the most sensitive scenario. The experimental data reported in this work, acquired with a state-of-the-art full ring PET scanner, provide a comprehensive and consistent basis for the benchmarking of PET signal calculation engines. In particular, they can support a fine-tuning of the underlying physics models used by the respective implementation and therefore improve the accuracy of PET-based therapy verifications at current and future treatment facilities.